The Effect of Service Quality and Promotion on Telkomsel Customer Satisfaction (A Study of College Students in Bandar Lampung) - Sindy Amarda; Maulana Agung P; M. Iqbal Harori (Cita konsultindo, 2026)
Indonesia has many providers offering internet access services and conveniences, one of which is Telkomsel. In using Telkomsel cards, consumers consider several factors. This study aims to determine the impact of several factors on customer satisfaction with Telkomsel provider cards in Bandar Lampung, particularly among university students. The factors studied include service quality and promotion. This study uses explanatory research with a quantitative approach. The research population consists of Telkomsel card customers and students in Bandar Lampung. The sampling technique used is proportional stratified random sampling by selecting 10 universities in Bandar Lampung and 100 respondents selected as research samples. Data were obtained through the distribution of questionnaires to respondents. The data analysis techniques used included descriptive analysis, classical assumption testing, and multiple linear regression analysis using the SPSS Statistics 30 application program. The results of the study showed that, partially, service quality and promotion had a significant effect on customer satisfaction. Then, simultaneously, service quality and promotion together had a significant effect on customer satisfaction. Keywords: service quality, promotion, customer satisfaction, Telkomsel